INTEGRATING ENACTIVE AND INTERCORPOREAL APPROACHES TO INTERACTION AND INTERACTION ANALYSIS: d/DEAF PERSONS AND ANIMALS. IN SEARCH OF THE ‘IN-BETWEEN’ AND ADEQUATE METHODOLOGIES - Anne GELHARDT (Studia Universitatis Babeș-Bolyai. Philosophia)
How does understanding occur in encounters of living beings? What is experienced by the interaction partners and what happens in the ‘In-Between’? And how can this be captured? In this paper an enactive approach to interaction is proposed with the focus on reciprocal inter-corporeal attunement and co-creation of meaning in a specific environment. As alternative framework this approach is applied to the interaction of d/Deaf persons and animals. In the interaction with an animal, verbal communication – which is challenging for d/Deaf persons – is of secondary importance, so this frame is well suited to focus on intercorporeal attunement. In the interaction discourse regarding d/Deaf persons as well as Human-Animal-Interaction the assessment of the interaction process as such and embodied research methodologies are scarcely to be found. With the enactive approach new perspectives on the mechanisms of interaction and the influencing conditions can be opened as well as new approaches to respective research options.